Cislunar CubeSats to Measure Radiation in Support for Human Space Exploration - Guardabasso, Paolo; Lizy-Destrez, Stéphanie (2021)
The intentions of space agencies and private entities alike are clear: humankind wants to establish its presence on and around the Moon. Plans for the exploration of the surface of Earth’s only natural satellite are established, with international accords and partnership being created around the globe. A new opportunity arises for the space community as national agencies are currently collaborating in the conception of a lunar orbiting station, symbolic successor of the International Space Station (ISS) currently on a Low Earth Orbit (LEO). This “Gateway” station, will serve multiple purposes, including supporting human and robotic activity on the lunar surface and scientific research in Lunar vicinity. It will be placed on a Near Rectilinear Halo Orbit around the second Earth Moon Lagrange point (EML), with its apoapsis over the lunar south pole [1]. In this zone, the radiation environment is not yet very well known: the station will be equipped with the ERSA and HERMES sensors suites to measure doses absorbed by the crews on the NRHO. Nevertheless, a complete cartography of the larger cislunar space is not yet available, but it would prove very useful for all future missions to the Moon. This paper discusses the preliminary design of a lunar CubeSat mission, developed by the Space Advanced Concepts Laboratory at the Institut Supérieur de l’Aéronautique et de l’Espace (ISAE-SUPAERO) in Toulouse, France. The mission, named DRACO (Detection of RAdiation in Cislunar space Orbit), considers two CubeSats deployed in the cislunar space to study its radiation environment, gaining knowledge for future crewed missions near the Earth-Moon Lagrange (EML) points, and proving the ability of nanosatellites to operate in this environment. Moreover, one of the key functions of the Gateway station will be the deployment of smaller spacecraft. This assumption will simplify the mission design for the DRACO CubeSats’ reduced propulsion and control capabilities, avoiding performing a lunar insertion manoeuvre. Once deployed from the Gateway, the two spacecraft will transfer to a neighbouring Near Rectilinear Halo Orbit, where they will remain for a calibration phase. They will then transfer to their science orbit, each reaching a larger Halo orbit around EML1 and EML2. The orbit choice was done considering multiple parameters such as stability, station keeping costs etc., to determine the most cost efficient and goal-oriented orbit. Transfers have been studied within the Circular Restricted Three-Body Problem (CR3BP) model, which introduces some simplifications in the relative motion between the Earth and the Moon, while maintaining the fundamental dynamical behaviours of a multibody system. A search for a transfer sequence was carried out, to find the best design with respect to the mission requirements, also considering the limited amount of fuel available and the mission lifetime. Moreover, the advantage of invariant manifolds, natural dynamical structures that provide low-cost transfer in the cislunar space, was evaluated. Finally, the disposal of spacecraft was discussed, in search for a feasible solution, sustainable for the future debris environment. The main DRACO mission objective is to characterise the radiation environment around the Moon. To achieve this, CubeSats were equipped with a suitable payload to perform full field ion measurements, observing the ion spectra to potentially validate different Galactic Cosmic Rays (GCRs) and Solar Particle Events (SPEs) models. Environmental models available in the literature were considered as basis for this analysis [2]. The performance of the CubeSats in the radiation environment is also assessed performing a sectoral analysis on the different subsystems of the nanosatellites. A complete Computer Aided Design (CAD) model with all required components was analysed with the advanced radiation dose analysis and shielding optimization software, FASTRAD [3]. The results of these studies led to the creation of a preliminary design of the two CubeSats. Moreover, different widths for the external panels of the spacecraft were considered, to provide the best trade-off between radiation protection and mass. References [1] J. Williams, D. E. Lee, R. J. Whitley, K. A. Bokelmann, D. C. Davis, and C. F. Berry, ‘Targeting Cislunar Near Rectilinear Halo Orbits for Human Space Exploration’, presented at the 27th AAS/AIAA Space Flight Mechanics Meeting, San Antonio, Texas, Feb. 2017. [2] M. A. Xapsos, P. M. O'Neill and T. P. O'Brien, "Near-Earth Space Radiation Models," in IEEE Transactions on Nuclear Science, vol. 60, no. 3, pp. 1691-1705, Jun. 2013, doi:10.1109/TNS.2012.2225846. [3] P. Pourrouquet, J.-C. Thomas, P.-F. Peyrard, R. Ecoffet, and G. Rolland, ‘FASTRAD 3.2: Radiation Shielding Tool with a New Monte Carlo Module’, presented at the 2011 IEEE Radiation Effects Data Workshop, Las Vegas, NV, Jul. 2011. doi:10.1109/REDW.2010.6062530.